Assessing the Effectiveness of Sukoharjo Bawaslu in Electoral Oversight Amid Institutional Constraints - Lestari, Etik Sri; Faried, Femmy Silaswati; Zaelani, Aziz (Jurnal Ilmu Hukum Kyadiren, 2025)
This study is driven by the pressing need for effective and independent election oversight to ensure the 2024 General Election is conducted in a democratic, honest, and fair manner. The primary focus is to evaluate the institutional existence and performance of the Sukoharjo Regency General Election Supervisory Body (Bawaslu) in executing its supervisory functions across all stages of the electoral process, as well as to identify the strategies employed for preventing and addressing electoral violations. Utilizing an empirical legal approach, this research employs data collection methods including interviews, document analysis, and field observations. The findings reveal that Bawaslu Sukoharjo has generally fulfilled its duties and exercised its authority in accordance with constitutional mandates and prevailing regulations. Nevertheless, the institution continues to encounter a range of structural, cultural, and technical challenges—most notably, limitations in human resources, budget constraints, and low levels of public participation. In conclusion, the effectiveness of electoral supervision is strongly influenced by the enhancement of institutional capacity and the development of synergistic collaborations with other key stakeholders within the local electoral democracy ecosystem.